PENGARUH LATIHAN BERPASANGAN TERHADAP KEMAMPUAN PASSING ATAS PADA TIM BOLA VOLI PUTRA SMK MULTIMEKANIK MASMUR PEKANBARU - Asmariadi Asmariadi; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Based on the observation that researchers did in male team of volleyball SMK Multimekanik Masmur Pekanbaru, it was shown that the ability of passing on was still not good. It was proved when they were on training or in matches, when they received an attack from the opponent team, when the ball bounced, and when given the ball passing over, the ball was not easy to be reached by their team mates. It is caused because the lack of training techniques of passing on male volleyball of SMK Multimekanik Masmur Pekanbaru. To train the passing ability on the male volleyball team of SMK Multimekanik Masmur Pekanbaru, they were given passing drills on pairs. The population in this research was SMK Multimekanik Masmur male volleyball team which consisted of 12 people. This type of research was an experiment to see the effect of this form of exercise. The sampling technique used total sampling, where the total population sampled. The data collection techniques derived from Pre-test and post-test. The instrument of the research used pair drils excercise. The data analyzed by using t-test. Based on data analysis and discussion, as evidenced by Tcount was 8.51 and Ttabel was 1.796. It means TCount> Ttabel. At level ɑ = 0.05. It can be concluded that there is a significant effect of exercise in pairs in team passing at SMK Multiteknik Masmur Pekanbaru.Keywords : exercises in pairs, passing ability.